Penentuan Waktu Optimum Dalam Pembuatan Bioetanol Dari Bonggol Pisang Tanduk(Musa paradisiaca formatypisa) Melalui Fermentasi - Setiawati, Eka Lilis; Gonggo, Siang Tandi; Abram, Paulus Hengky (Jurnal Akademika Kimia, 2016)
Banana tuber contains 76% starch as a source of organic material that can be changed to bioethanol which is an alternative of fuel oil. This study aimed to determine the optimum time of fermentation in the process of producing bioethanol from banana (musa paradisiaca formatypisa) tuber. In this study the fermentation of banana tuber is determined using saccharomyces cereviseae with the variation time of 3, 4, 5, 6, 7, 8 and 10 days. The stages carried out in this study were preliminary or sample preparation, delignification, hydrolysis, fermentation and separation. Bioethanol from the fermented ricestraw was analyzed using alcoholmeter. The content of bioethanol product increased on days 3 to 7 and reach the optimum on the day 7 which was 8.90%, where on the day 8 and 10 decreased the ethanol content.